Is ringgit really influenced by crude oil price? Evidence from commodity and bank lending markets - Mónica de Castro-Pardo; Pascual Fernández Martínez; José Manuel Guaita Martínez; José María Martín Martín (Contemporary Economics, 2019)
This study aims to investigate the effects of crude oil price (COP) and base rate (BR) on the strength of the Ringgit (RM) against the US Dollar (USD). Within the framework of the international Fisher effect theory, the study employs yearly data from the Bloomberg Database over an observed period from 1984 through 2017. Using bivariate Engle-Granger cointegration test as an estimation tool, the study reveals the presence of a long-term relationship between the RM and COP. However, the results of the Granger Causality test show an absence of a dynamic relationship between them. From the second analysis between the RM and BR, the study finds the presence of both long-term and short-term relationships between them. Interestingly, the relationship is somewhat bidirectional. Overall, the study has suggested the relevance of the international Fisher effect in explaining how variations in the RM exchange rate are elucidated by the bank lending market. In addition, it is worth noting that both BR and COP exert a significant influence on the strength of the RM against USD over time.
Keywords: G15; F10; O11; 330; Bivariate cointegration test; Crude oil price; Malaysia base rate; Malaysia exchange rate; Granger causality test; error-correction term; International Fisher theory